Histopathological changes of the buccal mucosa and skin after botulinum neurotoxin intramuscular injection in rats (immunohistochemical study) - Gihan S. Hassan; Basant H. Abouzaid; Reda G. Saleh (BMC Oral Health)
Abstract Background A surplus of clinical studies focused mainly on the clinical impacts of botulinum neurotoxin type A disregarding the histopathological changes stemming from its injection. This study was designed to inspect the potential effects of botulinum neurotoxin type A injection on the skin and buccal mucosa in both the injected and non-injected sides after one week and one month as no available studies have addressed its histopathological effects. Methods Twelve rats were injected with a single injection of 2.5 U of botulinum neurotoxin type A intramuscularly near the angle of the mouth on the right side. After one week, six injected rats were euthanized, and tissue samples were obtained from both the injection (n = 6) and the non-injection (n = 6) sides. After 4 weeks, six injected rats were euthanized, and tissue samples were obtained from both the injection (n = 6) and the non-injection (n = 6) sides. Six rats served as non-injected controls (n = 6). Samples were prepared for histological and immunohistochemical examination with caspase-3. Results Caspase-3 expression showed a highly significant increase (P = 0.005) in staining intensity in specimens of one week as compared to one month groups. At the non-injected side, the overall caspase-3 immunostaining score showed a significant elevation (P = 0.03) after one-month of botulinum neurotoxin type A injection. Conclusion Botulinum neurotoxin type A injection was associated with degenerative changes in the buccal mucosa and skin, nevertheless these changes declined after one month in the injected side. More degenerative changes were depicted in the non-injected side and increased after one month. Therefore, botulinum neurotoxin type A injection may affect not only the patient’s needs and expectations but also their health.